Penerapan Restorative Justice terhadap Anak dalam Perspektif Sistem Peradilan Pidana Anak di Indonesia - Bunga Filonia, Fredella (Jurnal Hukum In Concreto, 2024)
The restorative justice approach has been adopted in Indonesia’s juvenile criminal justice system as part of legal reform that prioritizes the restoration of social relationships and the protection of children, rather than punitive measures. This study aims to analyze the implementation of restorative justice for children and to examine its conceptual framework within a criminal justice system oriented toward fairness and child protection. The research employs a normative legal method with statutory and conceptual approaches, through the analysis of regulations, legal doctrines, and previous studies. The findings reveal that although a legal foundation has been established through Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, the implementation of restorative justice remains constrained by regulatory disharmony, limited understanding among law enforcement personnel, and a lack of community involvement. The concept of restorative justice emphasizes dialogue, offender accountability, and victim participation as core principles in achieving equitable case resolution. This study recommends the strengthening of technical regulations, the enhancement of training for law enforcement officers, and increased cross-sectoral collaboration as strategic steps to realize a juvenile justice system that is more humane and focused on the protection of children’s rights.